Evaluation of European Society of Cardiology (ESC) 0/1-hour algorithm in the diagnosis of 90-day major adverse cardiovascular events: a multicenter United States cohort study. (25th November 2020) - Allen, B; Christenson, R; Cohen, S; Nowak, R; Wilkerson, G; Mumma, B; Madsen, T; McCord, J; Huis In 'T Veld, M; Massoomi, M; Stopyra, J; Montero, C; et al.
Abstract: Background: The ESC 0/1-hour algorithm using high sensitivity troponin (ESC 0/1-h) is a rapid triage protocol for diagnosing acute coronary syndrome, however the classification performance of the algorithm in the US population is uncertain. Further, evidence for the use of ESC 0/1-h in the long-term diagnosis of major adverse cardiovascular events (MACE) remains limited. Purpose: To evaluate the performance of the ESC 0/1-h algorithm in diagnosing 90-day MACE in a diverse US cohort. Methods: In this prospective, multicenter, observational cohort study, adult emergency department patients who were evaluated for suspected ACS were enrolled at eight sites in the US. Serial 1-hour blood samples were collected and high sensitivity troponin T (hs-cTnT) concentrations were measured in a central laboratory using the hs-cTnT assay. Primary outcome included major adverse cardiovascular events (MACE) within 90 (+30) days of enrollment. MACE defined as myocardial infarction (MI), cardiovascular or uncertain death, and coronary revascularization. Presence of MI and cardiovascular death were adjudicated by independent reviewers blinded to hs-cTnT results. Each participant was stratified to one of three risk groups as determined by ESC 0/1-h algorithm. Diagnostic classification performance metrics with exact confidence intervals (i.e. negative predictive value [NPV], positive predicted value [PPV], sensitivity, and specificity) were evaluated for each risk group where appropriate. Results: Among 1430 eligible participants, 45.8% (655/1430) were women and 36.6% (524/1430) were African American with a mean age of 57.6±12.8 years. MACE at 90-days occurred in 15.5% (221/1430). ESC 0/1-h stratified 59.5% (851/1430) subjects in Rule-Out range and 13.0% (186/1430) subjects in Rule-In range. The Rule-Out criteria had an NPV and sensitivity for 90-day MACE of 96.8% (95% CI: 95.4–97.9%) and 87.8% (95% CI: 82.7–91.8%), respectively. For 90-day cardiovascular death or MI, Rule-Out criteria had an NPV of 98.2% (95% CI: 97.1–99.0%) and sensitivity was 92.4% (95% CI: 87.8–95.7%). The Rule-In criteria had a PPV of 60.8% (95% CI: 53.3–67.8%) for both outcomes. Rule-In criteria had a specificity for 90-day MACE and 90-day cardiovascular death or MI of 94.0% (95% CI: 92.5–95.2%) and 94.1% (95% CI: 92.6–95.3%), respectively. Among the 27.5% (393/1430) participants classified in neither risk groups, the prevalence of 90-day MACE was 20.6% (81/393) and the prevalence of 90-day cardiovascular death or MI was 17.8% (70/393) Conclusion: In a prospective, multicenter, US cohort, the ESC 0/1-h algorithm was unable to achieve a sufficiently high NPV to safely exclude the diagnosis of MACE within 90 days after emergency department presentation. New hs-cTn algorithms specific to the US population may be warranted. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Roche Diagnostics